Leaf Hydraulic Conductance for a Tank Bromeliad: Axial and Radial Pathways for Moving and Conserving Water - North, Gretchen B.; Lynch, Frank H.; Maharaj, Franklin D.; Phillips, Carly A.; Woodside, Walter T. (Frontiers in Plant Science, 2013)
Plants in the Bromeliaceae known as tank bromeliads essentially lack stems and absorptive roots and instead take up water from reservoirs formed by their overlapping leaf bases. For such plants, leaf hydraulic conductance is plant hydraulic conductance. Their simple strap-shaped leaves and parallel venation make them suitable for modeling leaf hydraulic conductance based on vasculature and other anatomical and morphological traits. Plants of the tank bromeliad Guzmania lingulata were investigated in a lowland tropical forest in Costa Rica and a shaded glasshouse in Los Angeles, CA, USA. Stomatal conductance to water vapor and leaf anatomy related to hydraulic conductance were measured for both groups. Tracheid diameters and number of veins were used with the Hagen-Poiseuille equation to calculate axial hydraulic conductance. Measurements of leaf hydraulic conductance using the evaporative flux method were also made for glasshouse plants. Values for axial conductance and leaf hydraulic conductance were used in a model based on leaky cable theory to estimate the conductance of the radial pathway from the vein to the leaf surface and to assess the relative contributions of both axial and radial pathways. In keeping with low stomatal conductance and density, low vein density, and narrow tracheid diameters, leaf hydraulic conductance for G. lingulata was quite low in comparison with most other angiosperms. Using the predicted axial conductance in the leaky cable model, the radial resistance across the leaf mesophyll was predicted to predominate; lower, more realistic values of axial conductance resulted in predicted radial resistances that were closer to axial resistance in their impact on total leaf resistance. Tracer dyes suggested that water uptake through the tank region of the leaf was not limiting. Both dye movement and the leaky cable model indicated that the leaf blade of G. lingulata was structurally and hydraulically well-suited to conserve water.